1099 Normative Levels of Interleukin 16 in Umbilical Cord Blood. (October 2012) - Denihan, NM; Looney, AM; Boylan, GB; Walsh, BH; Murray, DM
Abstract : Background and Aims: The need for early and accurate prediction of outcome in Hypoxic-Ischemic Encephalopathy (HIE) remains critical. We have previously demonstrated that Interleukin 16 (IL-16) is raised in the umbilical cord blood of infants with moderate and severe HIE and has the potential to be developed as a predictive biomarker. Normal reference ranges for IL-16 in umbilical cord blood have not been previously described. The aim of this study was to determine normative levels of IL-16 in full term neonates using cord blood following uncomplicated deliveries. Methods: Full term infants were recruited as part of an ongoing birth cohort study, the Cork BASELINE Birth Cohort Study. All had cord blood drawn and bio-banked at –80°C, within 3 hours of birth. Samples were chosen based on Apgar scores (≥8 at 1min, ≥9 at 5min), duration of ruptured membranes < 24 h, temperature in labour ≤37°C, gestational age ≥37 weeks and birthweight centile ≥10%. Analysis was performed on plasma EDTA, using ELISA Quantikine® (R&D Systems, Europe). Results: The study consisted of samples from 48 infants with two different modes of delivery; unassisted vaginal delivery (n=12 male, n=12 female) and pre-labour elective caesarean section (n=12 male, n=12 female). The range of all samples was normally distributed between 87.0 and 114.6 pg/ml. Mean (SD) for IL-16 was 103.1 (± 21.9) pg/ml. Levels were not affected by gender or mode of delivery. Conclusion: For the first time we have described the expected range of cord plasma IL-16 levels in healthy term infants.